PERSEPSI MASYARAKAT DALAM PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI UNTUK MENANGGULANGI KEMISKINAN DI KANAGARIAN PADUKUAN KECAMATAN KOTO SALAK KABUPATEN DHARMASRAYA - Pamiluarsih, Dewi Putri (Pendidikan Geografi, 2014)
This study aimed to obtain the data, process, analyze and discuss the Peoples Perception In the National Community Empowerment Program PNPM Mandiri To Eradicate Poverty In Kenagarian Padukuan Salak Dharmasraya Koto subdistrict in view of the: 1) Program PNPM Mandiri National Community Empowerment Womens Savings and Loans and Results 2) Program PNPM Mandiri National Community Empowerment of Women and the Savings and Loans Non Results. This study pertained to a descriptive study. The study population was families who follow the PNPM independent in the field of women and non smpan loans savings and loans women who are in Kenagarian Padukuan Salak Dharmasraya Koto subdistrict. This research is spread on 3 ellipse. The research sample by random sampling technique of the population in the study area, sample data was collected using a numbering 91. guided questionnaire, the analysis used was descriptive statistics using a percentage formula. The results showed: 1) Public Perceptions About the National Program for Community Empowerment (PNPM) in the Field of Womens Savings and Loans To Tackle Poverty and result in Kenagarian Padukuan Koto subdistrict Dharmasraya Salak is good 2) Public Perceptions About the National Program for Community Empowerment (PNPM) Mandiri in the field of Womens Savings and Loans To Tackle Poverty and result in Kenagarian Padukuan Koto subdistrict Dharmasraya Salak is good.